Effect of synthetic biomass ash on high temperature corrosion behavior of super austenitic stainless steel 904L - Singh M.K.; Mahobia G.S.; Sinha O.P.; Singh V. (My University, 2025)
Cyclic hot corrosion behavior of the super austenitic stainless steel 904L was investigated in the temperature range 500 °C-650 °C, in synthetic biomass ash environment of alkali salts of NaCl, KCl, Na2SO4 and K2SO4, up to 100 h. Sample surface was mechanically polished and spray coated with alkali chlorides and sulfates with two different ratios of chlorine and sulfur, Cl:S = 40:60 with salt mixture SM1 and Cl:S = 60:40 with SM2, to 3-4 mg cm-2. The hot corrosion kinetics was studied by weight change of the salt coated samples and the corroded samples were characterized by SEM/EDS, XRD and EPMA. The hot corrosion rate of the samples coated with SM1 and SM2 at 500 °C was comparable and lowest. However, at higher temperatures from 550 °C-650 °C the rate of corrosion from SM2 was significantly higher than that from the SM1. The higher content of sulfur in SM1 reduced the severity of corrosion resulting from chlorine. There was significant difference in surface morphology of the samples corroded with SM1 and SM2 salt mixtures. The higher rate of hot corrosion from SM2, with higher ratio of Cl:S (60:40) was found to be associated with porosity developed in the protective oxide layer by volatile chlorides and consequent active oxidation of the material. © 2019 IOP Publishing Ltd.